Even a low transmitral pressure gradient after transcatheter mitral valve repair leads to impaired dynamic performance and increased left atrial endsystolic volumes. (8th February 2021) - Ziegler, L; Rieger, M; Gueder, G; Frantz, S; Nordbeck, P; Lengenfelder, B; Buravezky, L; Herrmann, S
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Transcatheter mitral valve repair (TMVR) was shown to be safe and improves outcome in patients with severe functional mitral regurgitation (MR). Mean transmitral pressure gradients (MVG) < 5.0 mmHg are generally tolerated after TMVR. However, the prognostic relevance of this arbitrary threshold remains unclear and dynamic changes during physical exercise are not well examined. METHODS: From 2017 to 2019 48 patients with an indication for TMVR were prospectively enrolled in a single center study. The total physical capacity was measured by dynamic stress echocardiography on bicycle at baseline, before discharge and follow-up (FUP, mean (± SD) of 8.2 ± 1.4 months). Patients were classified into two groups: "MVG present" (MVG ≥ 2.5mmHg, measured by transesophageal echocardiography intraoperatively after TMVR) or "MVG absent". Between group differences were compared with a two-sided t-test. For association analysis the Pearson Product-Moment correlation coefficient was used. RESULTS: 48 with a mean (± SD) age of 72.8 ± 12.1 years were eligible for the analysis. There was no significant difference in baseline characteristics concerning the level of the EuroScore II or prevalence of atrial fibrillation, heart failure, cardiovascular risk factors, renal failure or cardiomyopathy and demographic characteristics as age and sex, respectively. Also, most of the standard morphological and functional echocardiographic parameters as well as modern speckle-tracking derived parameters were similar between the 2 groups. There was no difference in remaining mitral regurgitation regarding severity between the two groups (p = 1.00). While the left atrial end systolic volumes (LAESV) at baseline did not differ significantly between groups, patients with an increased MVG after clipping showed an increase in LAESV (plus 56.2 ± 33.6 ml), while the other group showed a decrease in mean value (minus 15.9 ± 42.1 ml; baseline vs FUP: p < 0.001). Further performance in dynamic stress echocardiography was significantly better in patients without development of a gradient (increase in metabolic equivalent of task (METS) changes between FUP and baseline 1.05 vs 0.06, p = 0.014). Most importantly, those patients who had a higher MVG after TMVR showed a significant increase in MVG already during stress-echo at baseline, compared to patients who didn´t develop a significant MVG after intervention (1.45 ± 1, 08 mmHg vs. 0.67 ± 1, 00 mmHg; p = 0.026). CONCLUSION: After TMVR even a low MVG increase of > = 2.5mmHg is associated with impaired performance in dynamic stress echo and with enlargement of LAESV. Increase of MVG in stress echo at baseline may be suitable to identify patients at risk to develop pathological MVG. Therefore, periprocedural caution to hemodynamic changes in MVG should always be given. Maybe a certain residual MR could be accepted before implanting an additional clip, knowing that already a MVG > 2, 5 mmHg might have adverse effects.